Effectiveness of Papaya (Carica papaya) Leaf Extract Pills to Increase Breast Milk Production among Breasfeeding Women at Private Practice Midwife M Palangka Raya - Sofia Mawaddah (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Breast milk contains substances that are important and sufficient for the growth and development of infants. One of the efforts that can be performed to increase the rate of secretion and production of breast milk is through various types of (processed) food made from papaya leaves (Carica papaya). Papaya plants are widely grown throughout the tropics which contain the quercetin compound as a breast milk stimulant. This study aims to determine the effectiveness of papaya (Carica papaya) leaf extract pills to increase breast milk production among breastfeeding women. This was a pre-experimental study with One Group Pre-Test and Post-Test design. The population involved all women who exclusively breastfed infants aged 0-6 months at Private Practice Midwife Made, Palangka Raya City. The study samples consisted of 33 respondents who were selected using purposive sampling technique. Data were analyzed using the Paired sample T Test. The study results obtained z-statistics value of -5.011 with a probability of 0.000. Such findings showed that the probability value was < level of significance (a=5%). Thus, it can be concluded that there was a significant difference in infant weight before and after administration of papaya (Carica papaya) leaf extract pills among breastfeeding women.